What Do You See When You're Surfing? Using Eye Tracking to Predict Salient Regions of Web Pages - Buscher, Georg; Cutrell, Ed; Morris, Meredith Ringel (Proceedings of CHI 2009, 2009)
An understanding of how people allocate their visual attention when viewing Web pages is very important for Web authors, interface designers, advertisers and others. Such knowledge opens the door to a variety of innovations, ranging from improved Web page design to the creation of compact, yet recognizable, visual representations of long pages. We present an eye-tracking study in which 20 users viewed 361 Web pages while engaged in information foraging and page recognition tasks. From this data, we describe general location-based characteristics of visual attention for Web pages dependent on different tasks and demographics, and generate a model for predicting the visual attention that individual page elements may receive. Finally, we introduce the concept of fixation impact, a new method for mapping gaze data to visual scenes that is motivated by findings in vision research.